1899
DOI: 10.1021/j150010a002
|View full text |Cite
|
Sign up to set email alerts
|

The Dissociative Power of Solvents

Abstract: BY 1.01-1s KAHLEXRERG .isn AZ;\KIAH 'r. LISCOLS ' H. I]. Cacly, Jour. I'hys. Chetn. I , 707 (rS97). E, Rout?-, Cotnptes rendus,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1902
1902
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Research into the electrical conductivity (σ) of non-aqueous liquids began largely around the turn of the 20th century, following on from studies of ionic conduction in aqueous solutions. Early studies by Kahlenberg and Lincoln [26], and extended by Lincoln [27], demonstrated that the electrical conduction of salts increased with the increasing dielectric constant of the solvent, emphasizing the importance of dissociation and ionic conduction, even in non-aqueous environments. Subsequent researchers, for example Shaw [28] and Kraus and Fuoss [29], considered the electrical conductivity of organic salts in organic liquids from experimental and theoretical viewpoints.…”
Section: Electrical Conduction In Non-aqueous Liquidsmentioning
confidence: 99%
“…Research into the electrical conductivity (σ) of non-aqueous liquids began largely around the turn of the 20th century, following on from studies of ionic conduction in aqueous solutions. Early studies by Kahlenberg and Lincoln [26], and extended by Lincoln [27], demonstrated that the electrical conduction of salts increased with the increasing dielectric constant of the solvent, emphasizing the importance of dissociation and ionic conduction, even in non-aqueous environments. Subsequent researchers, for example Shaw [28] and Kraus and Fuoss [29], considered the electrical conductivity of organic salts in organic liquids from experimental and theoretical viewpoints.…”
Section: Electrical Conduction In Non-aqueous Liquidsmentioning
confidence: 99%
“…Solvents with a carbonyl polar group are usually weak donors and as a consequence acid-base interactions occur to a slight extent only. Conductance results for the hydrohalide acids in aldehydes and ketones (25,37,106,177) (shown in figure 4) are limited and of qualitative nature only. Measurements are complicated by side reactions, e.g., aldol condensation, and stable electrical resistances are generally uncommon, e.g., the conductivity of hydrogen chloride increases with time in cinnamaldehyde (177) and acetone (132).…”
Section: Conductance Data For Hydrogen Halidesmentioning
confidence: 99%